Performance and design of OCDMA spectral-amplitude-coding with optical orthogonal codes - LI Chuan-qi; SUN Xiao-han; ZHANG Ming-de; DING Dong (Tongxin xuebao)
The scheme of FBGs-based OCDMA spectral-amplitude-coding（SAC） for OCDMA system with optical orthogonal code is discussed; The designing and the achievement process of SAC encoder/decoder with)1,1,1（）,,(2+++=qqqwNlare firstly submitted; The performance of this system, the SIR and BER resulted from multi-access interference （MAI）, are also analyzed in detail under the condition that the powers of code chips are not uniform; the applied foreground of this system is predicted.